KULIAH KERJA NYATA UNIVERSITAS JEMBER MEMBANGUN DESA KEMBANGKAN RUBUHA ATASI HAMA TIKUS DI DESA LICIN - Samudro, Fathan Setyo; Al Islami, Mohamad Riedho; Romadhani, Chita Shofiya; Lakonawa, Dino; Maghfiroh, Melinda Dwi; Marvintha, Kirana Ndaru; Wulandari, Amanda Eka; Janah, Febriyanti Alya; Huwae, Michelle Abelina; Pamungkas, Desika; Haryadi, Nanang Tri (PAPUMA: Journal of Community Services, 2025)
Rice field rat pest infestation (Rattus argentiventer) is the main obstacle in efforts to increase rice productivity in Indonesia, including Licin Village. Therefore, it requires a strategy with environmentally friendly, effective, and sustainable control. The University of Jember Village Building Real Work Lecture Activity in Licin Village offers a solution with an ecological approach through the use of owls (Tyto alba) as natural predators. Students and farmer groups carried out activities in several stages: socialization about the life cycle of rats and the benefits of owls, counseling on pest control, making owl houses, and installing Rubuha in rice fields. The Rubuha design is available in a standard size (50 x 50 x 50 cm) and is crafted from wood and plywood materials, featuring a protective roof to withstand rain. The results of the activity showed that the farmer groups responded positively to the use of owls as an alternative to rat pest control. Socialization and counseling increase farmers' knowledge about the life cycle of rats and the role of natural predators in agricultural ecosystems. The installation of Rubuha in strategic locations began to show signs of the presence of owls, although the adaptation process took time. Thus, the implementation of Rubuha through active community participation can be a sustainable solution in rat pest control in Licin Village. The success of the program is highly dependent on the continuity of monitoring, evaluation, and collaborative support from farmers, village governments, and related institutions in expanding the implementation in all rice fields.